Towards genomic newborn screening, part I: Mapping the ethical issues - Settegast, Sascha; Alex, Karla; Dikow, Nicola; Mütze, Ulrike; Schnabel-Besson, Elena; Doll, Elena Sophia; Mahal, Julia; Neth, Lars; Ditzen, Beate; Kölker, Stefan; Müller-Terpitz, Ralf; Schaaf, Christian P.; et al. (Ethik in der Medizin, 2025)
Newborn screening (NBS) is an internationally successful program for the secondary prevention of rare congenital diseases. At present, most of the target conditions in NBS are diagnosed by biochemical markers. Recent advances in genomic sequencing and in the bioinformatic evaluation of genetic variants will soon make it feasible however to expand NBS significantly by testing newborns directly for pathogenic variants. Yet, genomic newborn screening (gNBS) raises important ethical issues that require resolution, given that several pilot studies on gNBS implementation are already underway. Given a rapidly growing scholarly engagement with the ethics of gNBS, a more systematic and comprehensive mapping of the ethical issues and considerations relevant to gNBS is needed to move the debate forward at this point.